Marketing Mix and Community Product Purchase Behavior During Covid-19 Pandemic in Surabaya - Nanik Hariyana; Wilma Cordelia Izaak (Future Science, 2021)
During stable times, firms will generally aim to create reliable B2B relationships that provide increased efficiency and profitability. However, tumultuous times, such as the time during a major pandemic, cause many significant disruptions in both internal and external environmental domains. Thus, we argue that it is critical during this time to reevaluate the company's business relationships as a whole. While long-term partnerships are great for handling incremental changes during stable times, disruptive environmental changes may require managers to consider disruptive changes to their businesses. A pandemic may also present opportunities for establishing new relationships as there may be other partners/suppliers who are better equipped to help the company address urgent short-term needs and to capitalize on significant long-term opportunities. In this paper, we design a new relationship audit template to help B2B firms weather the immediate crisis at hand and position themselves more strategically for the future. We explore this idea about the coronavirus outbreak, introduce the idea of a B2B crisis relationship audit, and offer potential steps forward for firms.